The Effect of Using Bamboo Dancing Cooperative Learning Strategy Towards Student English Speaking Skill in Senior High School 3 Jambi City - Yozi Sonor Gita; Yanti Ismiyati (JELT: Journal of English Language Teaching, 2021)
The purpose of this study was to find out the effect or not there was any effect of using Bamboo Dancing Cooperative Learning towards Student English Speaking Skill. The problem in this study referred to the learning strategy English speaking skills. The study was conducted at the MIPA 6 and MIPA 7 in senior high school. The population of the study was 71 student in the second semester of MIPA 6 and MIPA 7. The sample of this study was all of the 36 is MIPA 6, 22 female and 14 male students. The types of the data were quantitative. The data were obtained by using tell the recount text from the picture to test the speaking of students, and analyzed by using manual effect analysis with speaking table score, oral proficiency scoring categories. Furthermore based on statistical compulation t-test was found that the coefficient of  = 4,05 where the coefficient of = 1,994. It means that there significant effect of using bamboo dancing method toward students’ english speakig skill. It also indicated that there significant effect of using Bamboo Dancing Cooperative Strategy Towards Students English Speaking Skill in Senior High School 3 Jambi City in 2020-2021 Academic Year.Keywords: Speaking, Bamboo Dancing, Cooperative Learning Strategy